Role of myostatin promoter mutations in growth and molting regulation of Macrobrachium rosenbergii - Su, Qiyao; Wei, Jie; Wang, Yakun; Liufu, Bai; Li, Huarong; Mai, Zhuang; Hong, Kunhao; Zhou, Qiaoyan; Jiao, Tianhui; Mu, Xidong; Yu, Lingyun (Frontiers in Marine Science, 2025)
Myostatin (Mstn), a negative regulatory factor in myocytes, has garnered significant attention. This study focused on the Mstn gene and its 24-base-pair mutant in the promoter region of the giant freshwater prawn (Macrobrachium rosenbergii), aiming to investigate the regulatory roles of Mstn and its mutant in M. rosenbergii. The research provides theoretical insights into the functional mechanisms of Mstn in crustaceans. Spatiotemporal expression patterns revealed Mstn presence throughout embryonic development and in various body tissues, with peak expression during the gastrula stage and in the hepatopancreas. During the molting cycle, Mstn expression levels decreased in the order of post-molt (A phase), pre-molt (D3 phase), and molting (E phase). Knockdown experiments targeting two genotypes within the Mstn promoter region significantly reduced growth rates and extended molting cycles compared to control group. Further trials on the F2 generation confirmed these findings, highlighting that promoter knockdown influenced the expression of three molting-related genes and slowed the growth rate of M. rosenbergii. This study clarifies the functional role of Mstn in crustacean growth and molting, providing a foundation for understanding its regulatory mechanisms and offering potential applications in aquaculture.